A fluorescence-activatable reporter of flavivirus NS2B–NS3 protease activity enables live imaging of infection in single cells and viral plaques - Arias Arias, Jorge Luis (2020)
The genus Flavivirus in the family Flaviviridae comprises many medically important viruses, such as dengue virus (DENV), Zika virus (ZIKV), and yellow fever virus. The quest for thera- peutic targets to combat flavivirus infections requires a better understanding of the kinetics of virus–host interactions during infections with native viral strains. However, this is precluded by limitations of current cell-based systems for monitoring flavivi- rus infection in living cells. In the present study, we report the construction of fluorescence-activatable sensors to detect the activities of flavivirus NS2B–NS3 serine proteases in living cells. The system consists of GFP-based reporters that become fluo- rescent upon cleavage by recombinant DENV-2/ZIKV proteases in vitro. A version of this sensor containing the flavivirus inter- nal NS3 cleavage site linker reported the highest fluorescence activation in stably transduced mammalian cells upon DENV-2/ ZIKV infection. Moreover, the onset of fluorescence correlated with viral protease activity. A far-red version of this flavivirus sensor had the best signal-to-noise ratio in a fluorescent Dulbec- co’s plaque assay, leading to the construction of a multireporter platform combining the flavivirus sensor with reporter dyes for detection of chromatin condensation and cell death, enabling studies of viral plaque formation with single-cell resolution. Finally, the application of this platform enabled the study of cell-population kinetics of infection and cell death by DENV-2, ZIKV, and yellow fever virus. We anticipate that future studies of viral infection kinetics with this reporter system will enable basic investigations of virus–host interactions and facilitate future applications in antiviral drug research to manage flavivi- rus infections.